2012
DOI: 10.1155/2012/150120
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Jaundice and Maternal Diet with Chinese Herbal Medicines

Abstract: Our objective was to identify the association between maternal diet with Chinese herbal medicines and prolonged jaundice of breast-fed infants. Healthy infants at 25 to 45 days of age were eligible for enrollment into this prospective study. Jaundice was defined as a transcutaneous bilirubin (TcB) value ≥ 5 mg/dL. A questionnaire survey asking feeding type, stool pattern, and maternal diet was conducted at the time of TcB measurement. A total of 1148 infants were enrolled, including 151 formula-fed, 436 combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In infants fed with breast milk, prolonged jaundice was very common. Our previous study demonstrated that, in breastfed infants, maternal diets are associated with prolonged jaundice 18 . The components of breast milk contribute to the development of prolonged jaundice 11 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In infants fed with breast milk, prolonged jaundice was very common. Our previous study demonstrated that, in breastfed infants, maternal diets are associated with prolonged jaundice 18 . The components of breast milk contribute to the development of prolonged jaundice 11 .…”
Section: Discussionmentioning
confidence: 94%
“…As a result of immaturity in metabolism of bilirubin, preterm infants are at great risk of prolonged jaundice 19 . Our previous study enrolling 1148 healthy infants indicated that prolonged jaundice was more common in infants with GA 34~36 w than those with GA 37~42 w 18 . Genetic variant of UGT1A1 may play an important role of prolonged jaundice in preterm infants 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Infants were routinely observed visually for the development of significant clinical jaundice. Bilirubin level was screened daily in all infants with non-invasive transcutaneous bilirubinmeter BiliCheck device (Spectrx Inc, Norcross, GA, USA) [ 11 ]. Serum bilirubin tests were performed with Unistat TM bilirubinmeter (Cambridge Instruments, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…(iv) Detailed medical history, physical examination, and necessary examinations were taken and other possible pathological jaundice was excluded. A total of 29 jaundiced pairs (TcB value ≥ 7.87 mg/dL at 42 days after delivery) and 65 controlled pairs (TcB value < 7.87 mg/dL at 42 days after delivery) [ 16 , 17 ] were eventually enrolled ( Figure 1 ). The study was approved by the Ethics Committee of the Peking University People’s Hospital, and parents were informed and agreed upon before enrollment.…”
Section: Methodsmentioning
confidence: 99%